Spatially Resolved Electric‐Field Manipulation of Magnetism for CoFeB Mesoscopic Discs on Ferroelectrics. (17th January 2018) - Ba, You; Liu, Yan; Li, Peisen; Wu, Liang; Unguris, John; Pierce, Daniel T.; Yang, Danni; Feng, Ce; Zhang, Yike; Wu, Hao; Li, Dalai; Chang, Yuansi; et al.
Abstract: Electric‐field control of magnetism in ferromagnetic/ferroelectric multiferroic heterostructures is a promising way to realize fast and nonvolatile random‐access memory with high density and low‐power consumption. An important issue that has not been solved is the magnetic responses to different types of ferroelectric‐domain switching. Here, for the first time three types of magnetic responses are reported induced by different types of ferroelectric domain switching with in situ electric fields in the CoFeB mesoscopic discs grown on PMN‐PT(001), including type I and type II attributed to 109°, 71°/180° ferroelectric domain switching, respectively, and type III attributed to a combined behavior of multiferroelectric domain switching. Rotation of the magnetic easy axis by 90° induced by 109° ferroelectric domain switching is also found. In addition, the unique variations of effective magnetic anisotropy field with electric field are explained by the different ferroelectric domain switching paths. The spatially resolved study of electric‐field control of magnetism on the mesoscale not only enhances the understanding of the distinct magnetic responses to different ferroelectric domain switching and sheds light on the path of ferroelectric domain switching, but is also important for the realization of low‐power consumption and high‐speed magnetic random‐access memory utilizing these materials. Abstract : Three types of magnetic responses induced by different types of ferroelectric (FE) domain switching are revealed, particularly, the first observation of 90° rotation of the magnetic easy axis induced by 109° FE domain switching. The result is significant for understanding the distinct magnetic responses to different types of FE domain switching and shedding light on the path of FE domain switching.